Preparation method and application of 3D printed porous composite scaffold

The porous composite scaffold with three-element doped hydroxyapatite was prepared by 3D printing technology, and combined with type I collagen and silk fibroin composite gel modification layer, the problems of bone regeneration and tumor suppression in the treatment of osteosarcoma in the prior art were solved, and the dual effects of bone defect repair and tumor suppression were achieved.

CN119838059APending Publication Date: 2025-04-18CENTRAL MEDICAL (HUBEI) CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202410456765.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-16
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously promote bone regeneration repair and inhibit tumor cell recurrence in osteosarcoma treatment, and there is a problem of delayed healing or non-healing at the bone implant site.

Method used

The three-element doped hydroxyapatite/polycaprolactone (PCL) composite scaffold with dense external structure and sparse internal structure was prepared by 3D printing technology, combining type I collagen and silk fibroin composite gel modification layer to simulate the soft and hard binding structure of natural bone, regulate the fate of stem cells, promote bone regeneration and inhibit the apoptosis of tumor cells.

Benefits of technology

It promotes bone defect repair while eliminating tumors, has excellent biocompatibility, good biological activity and good compressive strength, and significantly improves the effect of bone regeneration and inhibits osteosarcoma recurrence.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure HDA0004794464230000011
    Figure HDA0004794464230000011
Patent Text Reader

Abstract

The invention belongs to the field of biomedical materials, and particularly discloses a preparation method and application of a 3D printing porous composite scaffold. I-type collagen and silk fibroin composite gel is modified on a 3D printing three-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffold with a polydopamine coating, the three-element doped hydroxyapatite is synthesized by using a chemical precipitation method, and Mg < 2 + >, Sr < 2 + > and SeO3 < 2-> ions are doped in crystal lattices. The 3D printing porous composite scaffold provided by the invention effectively simulates the structure and function of soft and hard combination of natural bones, is helpful for regulating and controlling the stem cell fate to improve the bone regeneration process, repairs bone defects while eliminating tumors, and can be applied to bone defect repair or osteosarcoma treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of biomedical materials, and in particular to a preparation method and application of a 3D printed porous composite scaffold. Background Art

[0002] Clinically, the treatment of osteosarcoma is mainly through extensive resection of local tumor tissue, followed by filling the defect area with bioactive bone scaffold materials, and adjuvant radiotherapy and chemotherapy are required after surgery to inhibit tumor recurrence. A large amount of research data shows that after osteosarcoma is mostly resected, it is difficult to clean up the malignant tumor cells, and these remaining osteosarcoma cells are likely to cause tumor recurrence or recurrence in the later stage. In order to avoid this, most people perform local radiotherapy and chemotherapy after the bone defect area is repaired by implanted materials. If the bone implant repair material can both promote bone regeneration and repair and induce tumor cell apoptosis, then it will accelerate the bone healing process and reduce the recurrence rate of osteosarcoma.

[0003] Autologous bone transplantation is an alternative method for treating bone defects caused by osteosarcoma resection, but there are multiple problems such as donor site complications, immune rejection and limited supply, which limit its clinical application. Therefore, the development of artificial bone substitutes with the ability to repair bone defects caused by osteosarcoma and eliminate cancer cells has become a clinical problem that needs to be solved urgently.

[0004] Hydroxyapatite (HA) is the main inorganic component of human hard tissue and is widely used in clinical practice due to its excellent biocompatibility and osteoconductivity. However, it is difficult for HA alone to repair bone defects caused by osteosarcoma, and the composite functions of multi-element doped HA make it potential in repairing bone defects caused by osteosarcoma. Different trace elements play different roles in the growth and development of bone tissue. For example, zinc (Zn), manganese (Mn) and strontium (Sr) have good osteogenesis; magnesium (Mg), copper (Cu) and cobalt (Co) have excellent angiogenesis; silicon (Si) and boron (B) have osteogenesis and angiogenesis; selenium (Se) can promote bone tissue development, anti-tumor and anti-aging. It is reported that there are few studies on the use of three-element doped HA to treat osteosarcoma and repair bone defects.

[0005] Bone has a unique microstructure. Bone tissue is a hard and tough tissue, in which the hard inorganic components (mainly hydroxyapatite) are mainly responsible for support, protection and load-bearing; the soft organic components (collagen fibers, polysaccharides) play an important role in the proliferation and migration of stem cells. Therefore, effectively mimicking the "soft and hard combination" structure and function of natural bone can help regulate stem cells and promote bone regeneration.

[0006] Polycaprolactone (PCL) has the advantages of good biocompatibility, strong shape retention and slow degradation, but its bioactivity is not enough when directly applied to bone tissue engineering. 3D printing technology can be applied to bone tissue scaffolds to print personalized shapes and accurately fit the defect site; pores that are conducive to cell proliferation can be set through specific programs to enhance the osteoinductivity, osteoconductivity and bone regeneration of the scaffold. Although the PCL-HA composite scaffolds prepared by 3D printing technology currently have good compressive strength and biocompatibility, they cannot simulate the physiological microenvironment required for the growth of bone marrow stem cells due to the structural and functional limitations of the scaffold. In addition, the scaffold lacks active ligands, resulting in ineffective cell adhesion. At the same time, there are large micropores between the microfibers of the 3D printed scaffolds, resulting in rapid dissipation of nutrients. This dissipation hinders the long-term and stable nutrient supply for the development of host cells during tissue remodeling. In addition, the long-distance migration that stem cells cannot overcome makes it difficult to reconstruct bone defects of critical size.

[0007] Currently, the artificial bone repair materials widely used in clinical practice are difficult to combine the inhibition of osteosarcoma, biological activity and the physiological microenvironment effects required for simulating the bone tissue regeneration process, resulting in delayed bone healing or even non-healing at the bone implant site in many patients, the formation of osteosarcoma during bone growth, and even the occurrence of pseudoarthrosis or joint deformity. Summary of the invention

[0008] The purpose of this application is to provide a preparation method and application of a 3D printed porous composite scaffold to address the deficiencies of the prior art. The scaffold has a dense external structure and a sparse internal structure, effectively simulates the soft-hard structure and function of natural bone, helps to regulate the fate of stem cells to improve the bone regeneration process, and promotes bone defect repair while eliminating tumors.

[0009] In order to achieve the above objectives, this application is implemented through the following technical solutions:

[0010] A method for preparing a 3D printed porous composite scaffold, wherein a composite gel of type I collagen and silk fibroin is modified on a 3D printed three-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffold coated with polydopamine, wherein the three-element doped hydroxyapatite is synthesized by a chemical precipitation method, and the lattice is doped with Mg 2+ , Sr 2+ and SeO3 2- ion.

[0011] According to the above scheme, the preparation method of the above 3D printed porous composite scaffold comprises the following steps:

[0012] S1. Preparation of 3D printed tri-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffolds coated with polydopamine

[0013] S1.1 Synthesis of three-element doped hydroxyapatite powder using chemical precipitation method

[0014] S1.2 Add the obtained three-element doped hydroxyapatite powder (Mg / Sr / Se-HA) to the PCL solution, stir and mix thoroughly to obtain a three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) solution;

[0015] S1.3 The above three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) solution is 3D printed and freeze-dried to obtain a three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) composite scaffold;

[0016] S1.4 Add the above-mentioned three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) composite scaffold to the dopamine solution, react with magnetic stirring at room temperature for 24h~48h, wash the composite scaffold repeatedly with pure water 2~3 times, take out the scaffold and dry it in a forced air drying oven at 37℃~50℃ for 24h~48h to obtain a 3D printed three-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffold modified with polydopamine microsphere coating.

[0017] S2. Preparation of type I collagen and silk fibroin composite gel

[0018] S2.1 provides a type I collagen solution and a silk fibroin solution;

[0019] S2.3 The type I collagen solution and the silk fibroin solution are mixed evenly, and then added into the dopamine solution to obtain a composite gel of type I collagen and silk fibroin;

[0020] S3. Preparation of porous composite scaffolds

[0021] S3.1 Add the type I collagen and silk fibroin composite gel obtained in the above step S2 into a pre-customized mold, and the mold can be customized according to the required shape, size, etc.;

[0022] S3.2 Add the polydopamine-coated 3D printed three-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffold obtained in step S1 above into the above mold and place it for 3-12 hours;

[0023] S3.3 Place the above mold in a vacuum freeze dryer for freeze drying to obtain a porous composite scaffold.

[0024] Furthermore, the diameter of the three-element doped hydroxyapatite powder microspheres ranges from 0.5 μm to 5 μm; the synthesis steps of the three-element doped hydroxyapatite powders using the chemical precipitation method are as follows:

[0025] S1.1.1 respectively obtained Mg 2+ Ionic solution, Sr 2+ Ionic solution, SeO3 2- Ionic solutions, calcium salt solutions, phosphate salt solutions;

[0026] S1.1.2 SeO3 2- Add the ion solution to the phosphate solution, stir and mix, and adjust the pH to 10-11 with ammonia water; 2+ Ionic solution, Sr 2+ The ion solution is added to the calcium salt solution, stirred and mixed evenly, and then dripped into the above-mentioned phosphate salt solution through a peristaltic pump at a speed of 15rpm-50rpm, and stirred and reacted for 1-5h at 30°C-90°C in a double-layer glass reactor, and the pH of the reaction mixture system is adjusted to 10-11 with ammonia water. After the reaction is completed, it is allowed to stand and age at room temperature for 12-24h; the molar ratio of (Mg+Sr+Ca) / (P+Se) in the solution is controlled to be 1.67;

[0027] S1.1.3 The above-mentioned static aged solution is washed using a ceramic membrane testing machine until the pH value of the powder solution reaches 7.0-7.5; the powder solution is filtered by positive pressure to collect the powder; the powder is dried in a circulating oven at 80°C-100°C; after drying, the powder is ground and sieved to obtain a three-element doped hydroxyapatite powder (Mg / Sr / Se-HA), and the diameter of the powder microspheres ranges from 0.5μm to 5μm;

[0028] Preferably, Mg 2+ The compound of ions is magnesium chloride, containing Sr 2+ The compound of ions is strontium nitrate, containing SeO3 2- The ionic compound is sodium selenite, the calcium salt compound is calcium nitrate tetrahydrate, and the phosphate salt compound is diammonium hydrogen phosphate.

[0029] Furthermore, the phosphate concentration in the phosphate solution is 0.03-0.3 mol / L, and the calcium ion concentration in the calcium salt solution is 0.05-0.5 mol / L; the Mg doped into the hydroxyapatite 2+ The molar percentage of calcium ions is 0.1-5 mol%, and the Sr doped into hydroxyapatite 2+ The molar percentage of calcium ions is 1-10 mol%, and SeO3 doped into hydroxyapatite 2- The molar percentage of ions to phosphate ions is 1 to 10 mol%.

[0030] Furthermore, the mass ratio of PCL and Mg / Sr / Se-HA in the triple-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) solution in S1.2 is 3:1 to 9:1.

[0031] Furthermore, the PCL used in S1.2 may be selected from, but not limited to, PCL having a viscosity average molecular weight of 60000-90000. Specifically, the PCL solution may be prepared by dissolving PCL in dichloromethane, with a mass concentration of 50-95%.

[0032] Furthermore, the printing parameters of the 3D printing molding setting in S1.3 can be set to: material deposition speed: 5mm / s, extrusion speed: 0.09mm / min, printing layer thickness: 0.5mm, platform molding temperature: -20~4℃, air pressure: 100~300kpa, mesh diameter 0.4mm~0.8mm, and device needle diameter 0.4mm.

[0033] Furthermore, the mass concentration of dopamine in the dopamine solution is 0.1 to 20 mg / mL. Dopamine can undergo oxidative polymerization in an alkaline (pH>7.5) aerobic environment to form polydopamine nanospheres. As the pH increases, dopamine gradually undergoes self-polymerization to form polydopamine, and the color gradually changes from light brown to dark brown.

[0034] Furthermore, the preparation method of the dopamine solution is: dissolving tris(hydroxymethyl)aminomethane powder in deionized water, adjusting the pH to 7.5-10 by titration with dilute hydrochloric acid, dissolving dopamine hydrochloride powder in the tris(hydroxymethyl)aminomethane solution and stirring for 30-120 minutes to form a dopamine solution.

[0035] Furthermore, the freeze-drying process conditions in S1.3 are: pre-freezing at -20 to -80°C for 3 to 24 hours, and then freeze-drying at a temperature of -50 to 37°C and a pressure of 0.1 to 50 Pa for 24 to 72 hours.

[0036] Furthermore, the mass ratio of the silk fibroin to the collagen is (0.3-3): 1. The type I collagen solution is obtained by dissolving type I collagen in an acetic acid solution, such as a 0.05 mol / mL solution; the silk fibroin solution is obtained by dissolving silk fibroin in a lithium bromide solution or a calcium chloride ternary system solution, and the mass fraction of the silk fibroin can be 0.5%-30%.

[0037] A 3D printed porous composite scaffold, comprising a polydopamine-coated 3D printed three-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffold and a type I collagen and silk fibroin composite gel modified layer modified on the polydopamine-coated 3D printed three-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffold, having a dense external structure and a sparse internal structure, wherein the three-element doped hydroxyapatite lattice is doped with Mg 2+ , Sr 2+ and SeO3 2- ion.

[0038] Furthermore, Mg doped into hydroxyapatite 2+ The molar percentage of calcium ions is 0.1-5 mol%, further, 0.1%-3%, and further 1.5-3%. 2+ The molar percentage of calcium ions is 1-10 mol%, further, 1%-6%, and further 3-6%, and SeO3 doped into hydroxyapatite 2- The molar percentage of ions to phosphate ions is 1 to 10 mol%, further, 1 to 6%, and further, 2 to 6%.

[0039] Furthermore, the mass ratio of PCL and the three-element doped hydroxyapatite Mg / Sr / Se-HA is 3:1 to 9:1.

[0040] Furthermore, the mass ratio of silk fibroin to type I collagen is (0.3-3):1.

[0041] Furthermore, the type I collagen and silk fibroin composite gel layer is obtained by uniformly mixing a type I collagen solution and a silk fibroin solution and then adding the mixture into a dopamine solution.

[0042] The present invention also provides the use of the above-mentioned 3D printed porous composite scaffold in preparing a bone defect repair material for bone defect repair or a bone scaffold filling material for osteosarcoma treatment.

[0043] Compared with the prior art, this application has the following advantages:

[0044] The present invention modifies type I collagen and silk fibroin composite gel on a 3D printed three-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffold coated with polydopamine, and the provided 3D printed porous composite scaffold effectively simulates the structure and function of the soft-hard combination of natural bones, has excellent biocompatibility, good biological activity and good compressive strength, helps to regulate the fate of stem cells to improve the bone regeneration process, promotes bone defect repair while eliminating tumors, and has good effects of inhibiting osteosarcoma and promoting bone defect repair when used for bone defect repair or osteosarcoma treatment. It is based on the important role of magnesium in the early stage of bone growth in the bone metabolism process, and magnesium-doped hydroxyapatite has good biological activity and biocompatibility, strontium plays an important role in the mineralization process of bone tissue, the osteogenesis, osteoclasts and angiogenesis of osteoporotic bone regeneration, and selenium can promote bone growth and improve the mechanical properties of bones and promote normal cell growth, while inducing tumor cell apoptosis, and has great potential in bone repair materials and osteosarcoma treatment.

[0045] Among them: Polycaprolactone (PCL) in the 3D printed three-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffold with polydopamine coating has the advantages of good biocompatibility, strong shape retention ability and slow degradation rate. The Mg / Sr / Se-HA-PCL composite scaffold was prepared by 3D printing technology using three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) composite scaffold, which has good compressive strength, biocompatibility, inhibition of osteosarcoma and good biological activity.

[0046] The collagen and silk fibroin in the type I collagen and silk fibroin composite gel modification layer are both natural fibrous proteins with good biocompatibility and osteoinductive properties, which are beneficial to the adhesion, proliferation and secretion of extracellular matrix of seed cells on the surface of the material, accelerate the rapid fusion of the repair material and soft tissue, and stimulate the differentiation of chondrocytes and osteoblasts around the implantation site to form new bone tissue. The dopamine used in the type I collagen and silk fibroin composite gel modification layer itself is hydrophilic and has good adhesion, and can also help increase the adhesion of hydrophobic PCL to collagen and silk.

[0047] The polydopamine-coated 3D printed three-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffold and the type I collagen and silk fibroin composite gel modification layer are both modified with polydopamine, which can achieve a thin thickness and firm bonding when coating the surface of the substrate material, and make the surface obtain good hydrophilicity and adhesion, promote in vitro osteogenic differentiation and calcium mineralization, promote osteogenesis and increase bone integration. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0049] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0050] Figure 1 This is the powder X-ray diffraction pattern (XRD) of the 3D printed porous composite scaffold prepared in Example 1 of the present application.

[0051] Figure 2 This is a diagram showing the proliferation results of the 3D printed porous composite scaffold after co-culture with mouse bone marrow mesenchymal stem cells (mBMSCs) in the examples of this application.

[0052] Figure 3This is a diagram showing the proliferation results after co-culture of the 3D printed porous composite scaffold and cancer cells (MG63) in the example of this application.

[0053] Figure 4 This is a diagram for the in vivo osteogenesis evaluation of the 3D printed porous composite scaffold in the examples of this application. DETAILED DESCRIPTION

[0054] The following will be combined with specific implementation methods and examples to specifically describe the embodiments of the present invention, and the advantages and various effects of the embodiments of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementation methods and examples are used to illustrate the embodiments of the present invention, rather than to limit the embodiments of the present invention.

[0055] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the embodiments of the present invention belong. In the event of a conflict, this specification takes precedence.

[0056] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the embodiments of the present invention can be purchased from the market or prepared by existing methods.

[0057] It should be noted that, in this document, relational terms such as “first” and “second” are merely used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations.

[0058] According to the method for preparing a 3D printed porous composite scaffold of the present invention, the following embodiments are provided:

[0059] Example 1

[0060] A method for preparing a 3D printed porous composite scaffold, the specific steps of the preparation method are:

[0061] S1. Preparation of 3D printed tri-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffolds coated with polydopamine

[0062] S1.1 respectively obtain magnesium chloride solution, strontium nitrate solution, sodium selenite solution, calcium nitrate tetrahydrate solution, and diammonium hydrogen phosphate solution;

[0063] S1.2 Add sodium selenite solution to diammonium hydrogen phosphate solution, stir and mix, and adjust the pH to 10-11 with ammonia water; add magnesium chloride solution and strontium nitrate solution to calcium nitrate tetrahydrate solution, stir and mix evenly, then drop into the diammonium hydrogen phosphate solution at a speed of 37.5 rpm through a peristaltic pump, stir and react at 90°C for 3 hours in a double-layer glass reactor, adjust the pH of the reaction mixture to 10-11 with ammonia water, and let it stand and age at room temperature for 18 hours after the reaction is completed; control the concentration of diammonium hydrogen phosphate solution in the solution to 0.15 mol / L, and the concentration of calcium nitrate tetrahydrate solution to 0.25 mol / L; the Mg in the added magnesium chloride solution 2+ The molar percentage of calcium ions in the calcium nitrate tetrahydrate solution is 5 mol%, and the Sr in the added strontium nitrate solution is 2+ The molar percentage of calcium ions in the calcium nitrate tetrahydrate solution is 10 mol%, and the SeO3 in the sodium selenite solution added is 10 mol%. 2- The molar percentage of ions in the diammonium hydrogen phosphate solution is 10 mol %; the molar ratio of (Mg+Sr+Ca) / (P+Se) in the solution is 1.67;

[0064] S1.3 The above-mentioned static aged solution is washed using a ceramic membrane testing machine until the pH value of the powder solution reaches 7.0-7.5; the powder solution is filtered by positive pressure to collect the powder; the powder is dried in a circulating oven at 90°C for 24 hours; after drying, the powder is ground and sieved to obtain three-element doped hydroxyapatite powder (Mg / Sr / Se-HA);

[0065] S1.4 Add the obtained three-element doped hydroxyapatite powder (Mg / Sr / Se-HA) to the PCL solution (viscosity average molecular weight 60000), stir and mix thoroughly to obtain a three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) solution; the PCL solution is a solution of PCL dissolved in dichloromethane, with a mass concentration of 90%; the mass ratio of PCL to Mg / Sr / Se-HA in the three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) solution is 5:1;

[0066] S1.5 The above three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) solution was 3D printed and freeze-dried to obtain a three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) composite scaffold; the printing parameters of the 3D printing molding setting are: material deposition speed: 5mm / s, extrusion speed: 0.09mm / min, printing layer thickness: 0.5mm, platform molding temperature: 4°C, air pressure: 300kpa, mesh diameter 0.4mm, equipment needle diameter 0.4mm. The process conditions of freeze drying are: pre-freezing at -60°C for 3h, and then freeze drying at a temperature of -10°C and a pressure of 10Pa for 48h;

[0067] S1.6 Add the above three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) composite scaffold to the dopamine solution, react with magnetic stirring at room temperature for 24 hours, wash the composite scaffold repeatedly with pure water 2 to 3 times, take out the scaffold and dry it in a blast drying oven at 45°C for 48 hours to obtain a 3D printed three-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffold modified with polydopamine microsphere coating. Preparation of dopamine solution: Dissolve 0.121g of tris(hydroxymethyl)aminomethane powder in 100mL of deionized water, adjust the pH to 8.5 by titration with dilute hydrochloric acid, dissolve 200mg of dopamine hydrochloride powder in the tris(hydroxymethyl)aminomethane solution, mix and stir for 60min to form a dopamine solution.

[0068] S2. Preparation of biomimetic extracellular matrix type I collagen and silk fibroin composite gel

[0069] S2.1 respectively obtain a type I collagen solution and a silk fibroin solution; the type I collagen solution is obtained by dissolving type I collagen in a 0.05 mol / mL acetic acid solution, with a mass fraction of 0.5%; the mass fraction of silk fibroin in the silk fibroin solution is 5%, and the silk fibroin is dissolved in a lithium bromide solution or a calcium chloride ternary system solution;

[0070] S2.2 The above-mentioned type I collagen solution and silk fibroin solution are mixed evenly and then added to the dopamine solution to obtain a type I collagen and silk fibroin composite gel. The mass ratio of silk fibroin to the collagen is 7:3; Preparation of dopamine solution: Dissolve 0.121g of tris(hydroxymethyl)aminomethane powder in 100mL of deionized water, adjust the pH to 8.5 by titration with dilute hydrochloric acid, dissolve 200mg of dopamine hydrochloride powder in the tris(hydroxymethyl)aminomethane solution, mix and stir for 60min to form a dopamine solution.

[0071] S3. Preparation of porous composite scaffolds

[0072] S3.1 adding the type I collagen and silk fibroin composite gel obtained in step S2 above into a pre-customized mold;

[0073] S3.2 Add the polydopamine-coated 3D-printed three-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffold obtained in step S1 above into the above mold and place it for 3 hours;

[0074] S3.3 Place the above mold in a vacuum freeze dryer for freeze drying to obtain a porous composite scaffold. The freeze drying process conditions are: pre-freeze at -60°C for 3 hours, and then freeze dry at -10°C and 10Pa for 48 hours.

[0075] Example 2

[0076] A method for preparing a 3D printed porous composite scaffold, the specific steps of the preparation method are:

[0077] S1. Preparation of 3D printed tri-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffolds coated with polydopamine

[0078] S1.1 respectively obtain magnesium chloride solution, strontium nitrate solution, sodium selenite solution, calcium nitrate tetrahydrate solution, and diammonium hydrogen phosphate solution;

[0079] S1.2 Add sodium selenite solution to diammonium hydrogen phosphate solution, stir and mix, and adjust the pH to 10-11 with ammonia water; add magnesium chloride solution and strontium nitrate solution to calcium nitrate tetrahydrate solution, stir and mix evenly, then drop into the diammonium hydrogen phosphate solution at a speed of 45 rpm through a peristaltic pump, stir and react at 65°C in a double-layer glass reactor for 5 hours, adjust the pH of the reaction mixture system to 10-11 with ammonia water, and let it stand and age at room temperature for 24 hours after the reaction is completed; control the concentration of diammonium hydrogen phosphate solution in the solution to 0.27 mol / L, and the concentration of calcium nitrate tetrahydrate solution to 0.45 mol / L; the Mg in the added magnesium chloride solution 2+ The molar percentage of calcium ions in the calcium nitrate tetrahydrate solution is 3 mol%, and the Sr in the added strontium nitrate solution is 2+ The molar percentage of calcium ions in the calcium nitrate tetrahydrate solution is 5 mol%, and the SeO3 in the sodium selenite solution added is 2- The molar percentage of ions in the diammonium hydrogen phosphate solution is 5 mol%; the molar ratio of (Mg+Sr+Ca) / (P+Se) in the solution is 1.67;

[0080] S1.3 The above-mentioned static aged solution is washed using a ceramic membrane testing machine until the pH value of the powder solution reaches 7.0-7.5; the powder solution is filtered by positive pressure to collect the powder; the powder is dried in a circulating oven at 80°C for 48 hours; after drying, the powder is ground and sieved to obtain three-element doped hydroxyapatite powder (Mg / Sr / Se-HA);

[0081] S1.4 Add the obtained three-element doped hydroxyapatite powder (Mg / Sr / Se-HA) to the PCL solution (viscosity average molecular weight 80000), stir and mix thoroughly to obtain a three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) solution; the PCL solution is a solution of PCL dissolved in dichloromethane, with a mass concentration of 75%; the mass ratio of PCL to Mg / Sr / Se-HA in the three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) solution is 3:1;

[0082] S1.5 The above three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) solution was 3D printed and freeze-dried to obtain a three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) composite scaffold; the printing parameters of the 3D printing molding setting are: material deposition speed: 5mm / s, extrusion speed: 0.09mm / min, printing layer thickness: 0.5mm, platform molding temperature: 0℃, air pressure: 250kpa, mesh diameter 0.5mm, equipment needle diameter 0.4mm. The process conditions of freeze drying are: pre-freezing at -50℃ for 6h, and then freeze drying at a temperature of -15℃ and a pressure of 20Pa for 48h;

[0083] S1.6 Add the above three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) composite scaffold to the dopamine solution, react with magnetic stirring at room temperature for 36 hours, wash the composite scaffold repeatedly with pure water 2 to 3 times, take out the scaffold and dry it in a blast drying oven at 50°C for 24 hours to obtain a 3D printed three-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffold modified with polydopamine microsphere coating. Preparation of dopamine solution: Dissolve 0.121g of tris(hydroxymethyl)aminomethane powder in 100mL of deionized water, adjust the pH to 8.5 by titration with dilute hydrochloric acid, dissolve 250mg of dopamine hydrochloride powder in the tris(hydroxymethyl)aminomethane solution, mix and stir for 80 minutes to form a dopamine solution.

[0084] S2. Preparation of biomimetic extracellular matrix type I collagen and silk fibroin composite gel

[0085] S2.1 respectively obtain a type I collagen solution and a silk fibroin solution; the type I collagen solution is obtained by dissolving type I collagen in a 0.05 mol / mL acetic acid solution, with a mass fraction of 1%; the mass fraction of silk fibroin in the silk fibroin solution is 10%, and the silk fibroin is dissolved in a lithium bromide solution or a calcium chloride ternary system solution;

[0086] S2.2 The above-mentioned type I collagen solution and silk fibroin solution are mixed evenly and then added to the dopamine solution to obtain a type I collagen and silk fibroin composite gel. The mass ratio of silk fibroin to the collagen is 3:2; Preparation of dopamine solution: Dissolve 0.121g of tris(hydroxymethyl)aminomethane powder in 100mL of deionized water, adjust the pH to 8.5 by titration with dilute hydrochloric acid, dissolve 250mg of dopamine hydrochloride powder in the tris(hydroxymethyl)aminomethane solution, mix and stir for 80min to form a dopamine solution.

[0087] S3. Preparation of porous composite scaffolds

[0088] S3.1 adding the type I collagen and silk fibroin composite gel obtained in step S2 above into a pre-customized mold;

[0089] S3.2 Add the polydopamine-coated 3D-printed three-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffold obtained in step S1 above into the above mold and place it for 3 hours;

[0090] S3.3 Place the above mold in a vacuum freeze dryer for freeze drying to obtain a porous composite scaffold. The freeze drying process conditions are: pre-freeze at -50°C for 6 hours, and then freeze dry at -15°C and 20Pa for 48 hours.

[0091] Example 3

[0092] A method for preparing a 3D printed porous composite scaffold, the specific steps of the preparation method are:

[0093] S1. Preparation of 3D printed tri-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffolds coated with polydopamine

[0094] S1.1 respectively obtain magnesium chloride solution, strontium nitrate solution, sodium selenite solution, calcium nitrate tetrahydrate solution, and diammonium hydrogen phosphate solution;

[0095] S1.2 Add sodium selenite solution to diammonium hydrogen phosphate solution, stir and mix, and adjust the pH to 10-11 with ammonia water; add magnesium chloride solution and strontium nitrate solution to calcium nitrate tetrahydrate solution, stir and mix evenly, then drop into the diammonium hydrogen phosphate solution at a speed of 30 rpm through a peristaltic pump, stir and react at 75°C in a double-layer glass reactor for 4 hours, adjust the pH of the reaction mixture system to 10-11 with ammonia water, and let it stand and age at room temperature for 24 hours after the reaction is completed; control the concentration of diammonium hydrogen phosphate solution in the solution to 0.03 mol / L, and the concentration of calcium nitrate tetrahydrate solution to 0.05 mol / L; the Mg in the added magnesium chloride solution 2+ The molar percentage of calcium ions in the calcium nitrate tetrahydrate solution is 5 mol%, and the Sr in the added strontium nitrate solution is 2+ The molar percentage of calcium ions in the calcium nitrate tetrahydrate solution is 5 mol%, and the SeO3 in the sodium selenite solution added is 2- The molar percentage of ions in the diammonium hydrogen phosphate solution is 10 mol %; the molar ratio of (Mg+Sr+Ca) / (P+Se) in the solution is 1.67;

[0096] S1.3 The above-mentioned static aged solution is washed using a ceramic membrane testing machine until the pH value of the powder solution reaches 7.0-7.5; the powder solution is filtered by positive pressure to collect the powder; the powder is dried in a circulating oven at 85°C for 36 hours; after drying, the powder is ground and sieved to obtain three-element doped hydroxyapatite powder (Mg / Sr / Se-HA);

[0097] S1.4 Add the obtained three-element doped hydroxyapatite powder (Mg / Sr / Se-HA) to the PCL solution (viscosity average molecular weight 80000), stir and mix thoroughly to obtain a three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) solution; the PCL solution is a solution of PCL dissolved in dichloromethane, with a mass concentration of 60%; the mass ratio of PCL to Mg / Sr / Se-HA in the three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) solution is 7:1;

[0098] S1.5 The above three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) solution was 3D printed and freeze-dried to obtain a three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) composite scaffold; the printing parameters of the 3D printing molding setting are: material deposition speed: 5mm / s, extrusion speed: 0.09mm / min, printing layer thickness: 0.5mm, platform molding temperature: -4℃, air pressure: 200kpa, mesh diameter 0.6mm, equipment needle diameter 0.4mm. The process conditions of freeze drying are: pre-freezing at -50℃ for 12h, and then freeze drying at a temperature of -5℃ and a pressure of 15Pa for 48h;

[0099] S1.6 Add the above three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) composite scaffold to the dopamine solution, react under magnetic stirring at room temperature for 48 hours, wash the composite scaffold repeatedly with pure water 2 to 3 times, take out the scaffold and dry it in a blast drying oven at 40°C for 36 hours to obtain a 3D printed three-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffold modified with polydopamine microsphere coating. Preparation of dopamine solution: Dissolve 0.121g of tris(hydroxymethyl)aminomethane powder in 100mL of deionized water, adjust the pH to 9.0 by titration with dilute hydrochloric acid, dissolve 300mg of dopamine hydrochloride powder in the tris(hydroxymethyl)aminomethane solution, mix and stir for 90 minutes to form a dopamine solution.

[0100] S2. Preparation of biomimetic extracellular matrix type I collagen and silk fibroin composite gel

[0101] S2.1 respectively obtain a type I collagen solution and a silk fibroin solution; the type I collagen solution is obtained by dissolving type I collagen in a 0.05 mol / mL acetic acid solution, with a mass fraction of 1.5%; the mass fraction of silk fibroin in the silk fibroin solution is 5%, and the silk fibroin is dissolved in a lithium bromide solution or a calcium chloride ternary system solution;

[0102] S2.2 The above-mentioned type I collagen solution and silk fibroin solution are mixed evenly and then added to the dopamine solution to obtain a type I collagen and silk fibroin composite gel. The mass ratio of silk fibroin to the collagen is 3:7; Preparation of dopamine solution: Dissolve 0.121g of tris(hydroxymethyl)aminomethane powder in 100mL of deionized water, adjust the pH to 9.0 by titration with dilute hydrochloric acid, dissolve 300mg of dopamine hydrochloride powder in the tris(hydroxymethyl)aminomethane solution, mix and stir for 90min to form a dopamine solution.

[0103] S3. Preparation of porous composite scaffolds

[0104] S3.1 adding the type I collagen and silk fibroin composite gel obtained in step S2 above into a pre-customized mold;

[0105] S3.2 Add the polydopamine-coated 3D-printed three-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffold obtained in step S1 above into the above mold and place it for 3 hours;

[0106] S3.3 Place the above mold in a vacuum freeze dryer for freeze drying to obtain a porous composite scaffold. The freeze drying process conditions are: pre-freeze at -50°C for 12 hours, and then freeze dry at -5°C and 15Pa for 48 hours.

[0107] Comparative Example 1

[0108] In this comparative example, a method for preparing a 3D printed porous composite scaffold is provided, wherein the main material is hydroxyapatite without element doping; and the remaining steps are the same as those in Example 1.

[0109] Comparative Example 2

[0110] In this comparative example, a method for preparing a 3D printed porous composite scaffold, wherein the main material is single element Mg doped hydroxyapatite, and the lattice of hydroxyapatite is doped with only Mg 2+ ions; the remaining steps are the same as in Example 1.

[0111] Comparative Example 3

[0112] In this comparative example, a method for preparing a 3D printed porous composite scaffold, wherein the main material is single element Sr doped hydroxyapatite, and the lattice of hydroxyapatite is doped with only Sr 2+ ions; the remaining steps are the same as in Example 1.

[0113] Comparative Example 4

[0114] In this comparative example, a method for preparing a 3D printed porous composite scaffold, the main material is single-element selenium-doped hydroxyapatite, and the lattice of hydroxyapatite is only doped with SeO3 2- ions; the remaining steps are the same as in Example 1.

[0115] The XRF diffraction analysis results of the three-element doped hydroxyapatite of Example 1 to Example 3 are shown in the following table

[0116]

[0117]

[0118] XRF analysis shows that the actual doped ion content is lower than the theoretical calculated value, indicating that some ions remain in the mother liquor and are not fully doped into the crystal lattice.

[0119] Attached Figure 1 -Attached Figure 4 Related instructions

[0120] The X-ray diffraction pattern (XRD) of the three-element doped hydroxyapatite for preparing the 3D printed porous composite scaffold in Example 1 of the present application is as follows: Figure 1 As shown, it shows that the lattice of the obtained three-element doped hydroxyapatite powder is doped with Mg 2+ , Sr 2+ and SeO3 2- ions; relative to pure hydroxyapatite powder, the crystallinity is low (generally speaking, the smaller the background in the XRD graph, the higher the intensity of the diffraction peak, the sharper the diffraction peak, that is, the smaller the half-width, the better the crystallinity); relatively low crystallinity is conducive to the degradation of 3D printed porous composite scaffolds and the release of the three elements of magnesium, strontium and selenium.

[0121] The proliferation results of the 3D printed porous composite scaffold and mouse bone marrow mesenchymal stem cells (mBMSCs) after co-culture in the present application are as follows Figure 2 As shown in the figure, compared with the 3D printed porous composite scaffold without element doping (Comparative Example 1), the proliferation effect of each sample (Comparative Example 2, Comparative Example 3, Comparative Example 4 and Example 1) on mouse bone marrow mesenchymal stem cells was not obvious at 24 hours; compared with the 3D printed porous composite scaffold without element doping (Comparative Example 1), the single element Mg 2+ Doped 3D printed porous composite scaffold (Comparative Example 2), single element Sr 2+ Doped 3D printed porous composite scaffold (Comparative Example 3) and Mg 2+ , Sr 2+ and SeO3 2- The 3D printed porous composite scaffold (Example 1) co-doped with three ions has a proliferation effect on mouse bone marrow mesenchymal stem cells, indicating that the doping of single Mg 2+ Ion, single doped Sr 2+ Ions and Mg 2+ , Sr 2+ and SeO3 2- Ion co-doping can promote the proliferation of mouse bone marrow mesenchymal stem cells. 2- ions have an adverse effect on the proliferation of mouse bone marrow mesenchymal stem cells, and the effect is further aggravated with the extension of culture time. 2+ , Sr 2+ and SeO3 2-The three-element co-doping of ions can solve the problem of the adverse effect of single-doping selenium on the proliferation of mouse bone marrow mesenchymal stem cells, and achieve an unexpected effect of promoting the proliferation of mouse bone marrow mesenchymal stem cells to a certain extent.

[0122] The proliferation results of the 3D printed porous composite scaffold and cancer cells (MG63) after co-culture in the present application are as follows Figure 3 As shown in the figure, it can be seen that the doped Mg 2+ , Sr 2+ and SeO3 2- Ions (Example 1) had a significant inhibitory effect on cancer cells (MG63) at both 24h and 72h.

[0123] Combined with the above Figure 2 Analysis shows that the present invention uses Mg 2+ , Sr 2+ and SeO3 2- The three-element co-doping of Mg ions not only has excellent anti-cancer activity, but also can improve the proliferation of mouse bone marrow mesenchymal stem cells, overcoming the obvious adverse effect of single selenium doping on the proliferation of mouse bone marrow mesenchymal stem cells. 2+ , Sr 2+ and SeO3 2- The 3D printed porous composite scaffold obtained by co-doping of three elements with ions can be based on the fact that magnesium plays an important role in the bone metabolism process in the early stage of bone growth, and magnesium-doped hydroxyapatite has good bioactivity and biocompatibility. Strontium plays an important role in the mineralization process of bone tissue, and in the osteogenesis, osteoclastology and angiogenesis of osteoporotic bone regeneration. Selenium can promote bone growth and improve the mechanical properties of bone and promote the growth of normal cells, while inducing tumor cell apoptosis. It has great potential in bone repair materials and osteosarcoma treatment.

[0124] The in vivo osteogenesis evaluation results of the 3D printed porous composite scaffolds in the examples of this application (Example 1 and Comparative Example 1) are as follows Figure 4 As shown. One month after implantation of bilateral femoral condylar bone defects (Φ5mm×8mm) in New Zealand rabbits, the circular surface of the implant and the surrounding tissue were taken for HE staining. It can be seen from the figure that the area of ​​newly formed granulation tissue at the bone defect site of the sample of Example 1 is better than that of the comparative example 1 group, and relatively dense cells of various types (mesenchymal cells, macrophages and lymphocytes, etc.) can be observed at the defect site of the sample group of Example 1, which is conducive to the regeneration and repair of the defect site in the later stage.

[0125] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0126] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A method for preparing a 3D printed porous composite scaffold, characterized in that: The composite gel of type I collagen and silk fibroin was modified on a polydopamine-coated 3D-printed three-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffold. The three-element doped hydroxyapatite was synthesized by chemical precipitation method and the lattice was doped with Mg 2+ , Sr 2+ and SeO3 2- ion.

2. The preparation method according to claim 1, characterized in that: The specific steps include: S1. Preparation of 3D printed tri-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffolds coated with polydopamine S1.1 Synthesis of three-element doped hydroxyapatite powder using chemical precipitation method S1.2 Add the obtained three-element doped hydroxyapatite powder (Mg / Sr / Se-HA) to the PCL solution, stir and mix thoroughly to obtain a three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) solution; S1.3 The above three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) solution is 3D printed and freeze-dried to obtain a three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) composite scaffold; S1.4 Add the above-mentioned three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) composite scaffold to the dopamine solution, react with magnetic stirring at room temperature for 24h~48h, wash the composite scaffold repeatedly with pure water 2~3 times, take out the scaffold and dry it in a forced air drying oven at 37℃~50℃ for 24h~48h to obtain a 3D printed three-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffold modified with polydopamine microsphere coating. S2. Preparation of type I collagen and silk fibroin composite gel S2.1 provides a type I collagen solution and a silk fibroin solution; S2.3 The type I collagen solution and the silk fibroin solution are mixed evenly and then added into the dopamine solution to obtain a composite gel of type I collagen and silk fibroin; S3. Preparation of porous composite scaffolds S3.1 adding the type I collagen and silk fibroin composite gel obtained in step S2 above into a pre-customized mold; S3.2 Add the polydopamine-coated 3D printed three-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffold obtained in step S1 above into the above mold and place it for 3-12 hours; S3.3 Place the above mold in a vacuum freeze dryer for freeze drying to obtain a porous composite scaffold.

3. The preparation method according to claim 2, characterized in that: The diameter of the three-element doped hydroxyapatite powder Mg / Sr / Se-HA microspheres ranges from 0.5μm to 5μm; The specific steps of synthesizing three-element doped hydroxyapatite powder by chemical precipitation method are as follows: S1.1.1 respectively obtained Mg 2+ Ionic solution, Sr 2+ Ionic solution, SeO3 2- Ionic solution, calcium salt solution, phosphate salt solution; S1.1.2 SeO3 2- Add the ion solution to the phosphate solution, stir and mix, and adjust the pH to 10-11 with ammonia water; 2+ Ionic solution, Sr 2+ The ion solution is added to the calcium salt solution, stirred and mixed evenly, and then dripped into the above-mentioned phosphate salt solution through a peristaltic pump at a speed of 15rpm-50rpm, and stirred and reacted for 1-5h at 30°C-90°C in a double-layer glass reactor, and the pH of the reaction mixture system is adjusted to 10-11 with ammonia water. After the reaction is completed, it is allowed to stand and age at room temperature for 12-24h; the molar ratio of (Mg+Sr+Ca) / (P+Se) in the solution is controlled to be 1.67; S1.1.3 Wash the above-mentioned aged solution using a ceramic membrane testing machine until the pH of the powder solution reaches 7.0-7.5; The powder solution is filtered under positive pressure to collect the powder; The powder is dried in a circulating oven at 80°C to 100°C; after drying, it is ground and sieved to obtain a three-element doped hydroxyapatite powder (Mg / Sr / Se-HA), and the diameter of the powder microspheres ranges from 0.5 μm to 5 μm.

4. The preparation method according to claim 4, characterized in that: The phosphate concentration in the phosphate solution is 0.03-0.3 mol / L, and the calcium ion concentration in the calcium salt solution is 0.05-0.5 mol / L; 2+ The compound of ions is magnesium chloride, containing Sr 2+ The compound of ions is strontium nitrate, containing SeO3 2- The ionic compound is sodium selenite, the calcium salt compound is calcium nitrate tetrahydrate, and the phosphate salt compound is diammonium hydrogen phosphate.

5. The preparation method according to claim 4, characterized in that: Mg doped into hydroxyapatite 2+ The molar percentage of calcium ions is 0.1-5 mol%, and the Sr doped into hydroxyapatite 2+ The molar percentage of calcium ions is 1-10 mol%, and SeO3 doped into hydroxyapatite 2- The molar percentage of ions to phosphate ions is 1 to 10 mol%.

6. The preparation method according to claim 1, characterized in that: The viscosity average molecular weight of PCL is 60000-90000; the PCL solution is prepared by dissolving PCL in dichloromethane, and the mass concentration is 50-95%; the mass ratio of PCL to Mg / Sr / Se-HA in the three-element doped hydroxyapatite / polycaprolactone (Mg / Sr / Se-HA-PCL) solution is 3:1-9:1; The printing parameters of the 3D printing setting in S1.3 can be set as follows: material deposition speed: 5mm / s, extrusion speed: 0.09mm / min, printing layer thickness: 0.5mm, platform molding temperature: -20~4℃, air pressure: 100~300kpa, mesh diameter 0.4mm~0.8mm, equipment needle diameter 0.4mm; The mass concentration of dopamine in the dopamine solution is 0.1 to 20 mg / mL; The freeze-drying process conditions are: pre-freezing at -20 to -80°C for 3 to 24 hours, and then freeze-drying at a temperature of -50 to 37°C and a pressure of 0.1 to 50 Pa for 24 to 72 hours.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the silk fibroin to type I collagen is (0.3-3):

1.

8. A 3D printed porous composite scaffold, characterized in that: The invention is composed of a polydopamine-coated 3D printed three-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffold and a type I collagen and silk fibroin composite gel modified layer on the polydopamine-coated 3D printed three-element doped hydroxyapatite / polycaprolactone (PCL) composite scaffold, having a dense external structure and a sparse internal structure, wherein the three-element doped hydroxyapatite lattice is doped with Mg 2+ , Sr 2+ and SeO3 2- ion.

9. The 3D printed porous composite scaffold according to claim 8, characterized in that: Mg doped into hydroxyapatite in three-element doped hydroxyapatite 2+ The molar percentage of calcium ions is 0.1-5 mol%, and the Sr doped into hydroxyapatite 2+ The molar percentage of calcium ions is 1-10 mol%, and SeO3 doped into hydroxyapatite 2- The molar percentage of ions to phosphate ions is 1 to 10 mol%.

10. Use of the 3D printed porous composite scaffold according to claim 1 in preparing a bone defect repair material for bone defect repair or a bone scaffold filling material for osteosarcoma treatment.

Citation Information

Cited By

  • Directional multifunctional bone repair scaffold prepared by pulling-folding method and preparation method and application thereof

    CN120514925A

  • A directional multifunctional bone repair scaffold prepared by a pull-folding method and a preparation method and application thereof

    CN120514925B

  • High-compatibility bioactive glass composite material and preparation method thereof

    CN121622983A

  • Highly compatible bioactive glass composites and methods of making the same

    CN121622983B